Adult T-cell leukemia/lymphoma and systemic cryptococcosis: Report of two cases in a Peruvian hospital - Altamirano-Molina, Milagros A. (2019)
Adult T-cell leukemia/lymphoma (ATLL) is a lymphoid neoplasm caused by the human T-cell lymphotropic virus type 1 (HTLV-1), an endemic retrovirus in our country. It has a heterogeneous presentation, with sub types of poor prognosis, and opportunistic infections that worsen the prognosis. We present two cases with aggressive varieties of the disease (acute and lymphomatous) complicated by systemic cryptococcosis. It is necessary to conduct a complete diagnostic approach and continuous monitoring of opportunistic agents in patients with ATL adapted to our epidemiological context.